Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Nasabah Dan Keputusan Sebagai Variabel Intervening Pada Bank Syariah Indonesia KCP Palembang Simpang Patal - Vineilia Dwi Ariantika; Lemiyana; Citra Lestari (CV. ITTC INDONESIA, 2024)
Customer satisfaction is an important factor that is used as a goal by companies, including the banking world. Customer satisfaction is very valuable for a bank or company. In customer satisfaction, there are several factors that influence it, including the quality of service and facilities. Customers who are satisfied with a service or product provided and the facilities are good and adequate tend to use the service again in the future. Before using services or products at a bank, customers will make a decision to use a bank's products and services. In this case, individuals will have their own perceptions, with individuals looking for information about bank services and products that suit their needs. This research aims to determine the influence of service quality and facilities on customer satisfaction where decisions are an intervening variable at Bank Syariah Indonesia KCP Palembang Simpang Patal. The method used in collecting data is through a questionnaire using a Likert scale. The population was 19,639 total customers from 2020 and the sample used was 99 respondents using a purposive sampling technique. Data processing uses the SmartPLS application version 4.0. The path coefficient shows that the quality of service and facilities has a significant effect on customer satisfaction. Decisions cannot mediate service quality on customer satisfaction. But decisions can mediate facilities on customer satisfaction